Biogas Energy - Abbasi, Tasneem; Tauseef, S.M; Abbasi, S.A (SpringerBriefs in Environmental Science, 2012)
In recent years, the importance of biogas energy has risen manifold and has become universal. This is due to the realization that biogas capture and utilization has great potential in controlling global warming. By capturing biogas wherever it is formed, we not only tap a source of clean energy, but we also prevent the escape of methane to the atmosphere. Given that methane has 25 times greater global warming potential than CO2, methane capture through biogas energy in this manner can contribute substantially towards global warming control.